TanYeah8D
10

# Solve the equation 4x^2-12x=7 algebraically for x.

(2) Answers
creepers20903

4x² - 12x = 7                                       - 7  - 7                        4x² - 12x - 7 = 0                 4x² + 2x - 14x - 7 = 0 2x(2x) + 2x(1) - 7(2x) - 7(1) = 0           2x(2x + 1) - 7(2x + 1) = 0                     (2x - 7)(2x + 1) = 0        2x - 7 = 0    or    2x + 1 = 0            + 7 + 7                 - 1  - 1              2x = 7                 2x = -1               2     2                  2      2                x = 3¹/₂      or       x = ⁻¹/₂

mariahmartinez13592

First subtract 7 from each side of the equation. 4x^2 - 12x - 7 = 0. Now we can substitute terms into our friend the quadratic equation, which you should memorize.  Or we can try a few simple factors.  7 is prime, so to make -7 one number must be positive and one must be negative. The first pair I tried, (2x + 1)(2x - 7) yield a middle term of -12x.  Therefore, setting each to zero yields:  x = -1/2, or x = 7/2.

Add answer